Solução Analítica da Equação de Difusão-Advecção com Coeficiente de Difusão Variável com o Tempo - Arbage, Maria Cristina A.; Vilhena, Marco Túllio; Buske, Daniela; Quadros, Régis S.; Moreira, Davidson M. (Ciência e Natura, 2011)
.